Autoimmune Thyroid Disease in Specific Genetic Syndromes in Childhood and Adolescence - Kyritsi, Eleni Magdalini; Kanaka-Gantenbein, Christina (Frontiers in Endocrinology, 2020)
Autoimmune thyroid disease (ATD) is the most frequent cause of acquired thyroid dysfunction, most commonly presenting either as Hashimoto’s thyroiditis or Graves’ Disease. Hashimoto’s thyroiditis is characterized by the presence of thyroid-specific autoantibodies, more commonly anti-thyroperoxidase antibodies in the serum and the typical inhomogeneous echostructure of the thyroid on a thyroid ultrasound examination. Hashimoto’s thyroiditis can for a long time be accompanied by normal thyroid function and hypothyroidism can only progressively be established. Graves’ disease is much less frequent in childhood and adolescence and presents with overt hyperthyroidism. After the onset of puberty, autoimmune thyroid disease affects females with a higher incidence than males, while during the prepubertal period there is not such a clear preponderance of affected females. Autoimmune thyroid disease can occur either isolated or in the context of other autoimmune disorders, such as type 1 Diabetes mellitus, celiac disease, alopecia areata, vitiligo, etc. Especially at the pediatric age, a higher incidence of autoimmune thyroid disease is also observed in the context of specific genetic syndromes, such as trisomy 21 (Down syndrome), Klinefelter syndrome or Turner syndrome. Nevertheless, although thyroid dysfunction may also be observed in other genetic syndromes, such as Prader-Willi or Williams or Di George syndrome, the thyroid dysfunction in these syndromes is not the result of thyroid autoimmunity. In this review article the incidence, as well as the clinical manifestation and accompanied pathologies of autoimmune thyroid disease in specific genetic syndromes will be presented and regular follow-up for the early identification of the disorder will be proposed.